2020
DOI: 10.1186/s12902-020-0510-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic syndrome using phenotypes consisting of triglyceride levels with anthropometric indices in Korean adults

Abstract: Background: The metabolic syndrome (MetS) has shown strong associations with the hypertriglyceridemic waist (HW) phenotype. The best anthropometric indicator of MetS remains controversial. Furthermore, no studies have investigated alternative indices that could replace waist circumference in the HW phenotype. The objectives of this study were to find the best indicator of MetS among anthropometric indices and to examine the predictive power of phenotypes consisting of triglyceride levels with anthropometric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26]33,34,45 Confirming earlier studies, the present study showed significant associations of HW phenotype with the presence of MetS. 16,22,23,25 In those studies, they only used the specific range of WC and TG values to the diagnosis of HW phenotype. Lee et al reported that it was difficult to find the better phenotype consisting of individual measurements and TG on basis of the specific range of TG and WC, 18 indicating that the qualitative nature of HW phenotype may to some extent attenuate its effectiveness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[16][17][18][19][20][21][22][23][24][25][26]33,34,45 Confirming earlier studies, the present study showed significant associations of HW phenotype with the presence of MetS. 16,22,23,25 In those studies, they only used the specific range of WC and TG values to the diagnosis of HW phenotype. Lee et al reported that it was difficult to find the better phenotype consisting of individual measurements and TG on basis of the specific range of TG and WC, 18 indicating that the qualitative nature of HW phenotype may to some extent attenuate its effectiveness.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, Lee et al have suggested that the best indicators of MetS in terms of individual anthropometric indices and the various phenotypes combining a single anthropometric index with TG may differ subtly according to age group in women other than in men in their latest report. 16 In this study, we also found that the ability of WTI, HW phenotype and TyG to screen for MetS may differ between genders. Unlike those studies, we transformed the qualitative HW phenotype into a specific continuous variable (WTI), and found that the one-SD increment of WTI significantly increased the odds of MetS in both genders.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Recent reports have defined HWP as follows: TG level ≥ 1.50 mmol/L and WC ≥ 85cm in women. 16 Therefore, women with TG level< 1.50 mmol/L or WC < 85cm were regarded as not having HWP.…”
Section: Participants and Methodsmentioning
confidence: 99%